PEMBANGUNAN PERTANIAN SEBAGAI UPAYA MENINGKATKAN PEREKONOMIAN DI PEDESAAN - Wijaya, Atika (Faculty of Social Science, Universitas Negeri Semarang, 2009)
Agriculture becomes major revenues of rural economic in Indonesia. However, more than 50 percentÃ‚Â poor people in Indonesia are farmer. In order to increasing rural economic especially to farmer, IndonesianÃ‚Â government need to made some stategic plans of agriculture development. Agriculture and rural economicÃ‚Â are two things that effects each other. If agriculture production decreasing then rural economic wasÃ‚Â decreasing too indirectly. In this article, enclose some recommendation to agriculture development inÃ‚Â Indonesia. There are agriculture diversifcation, empowerment of farmer itself, developing agricultureÃ‚Â technology, Ã‚Â and Ã‚Â new model Ã‚Â of Ã‚Â agriculture Ã‚Â that Ã‚Â is Ã‚Â organic Ã‚Â farming. Main Ã‚Â focus Ã‚Â is Ã‚Â in Ã‚Â deversifcationÃ‚Â agriculture so the farmer could get extra incomes from their farming. The most important is the governmentsÃ‚Â should give opportunity and access widely to agriculture sector and farmers.Keywords: Agriculture development, rural economic, farmerÃ¢â‚¬â„¢s income